(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The doubling of the global use of raw materials in the last century is an established environmental emergency due to an all too common “take – make – dispose” linear development model. Strategic plans within the Green Deal, such as the Circular Economy Action Plan, highlight the key role of building design as an enabling driver for process cyclicality. Against this backdrop, the paper describes the results of an experimental research project aimed at the technological design of a “circular” housing model. The integration of circular economy principles into the design process was pursued through the technology transfer of Additive Manufacturing principles as an enabling technology of Industry 4.0. The research is based on the first phase of critical analysis of two types of case studies: one referring to Circular Buildings, the other referring to 3D printed buildings, through a common reading method based on “circular” indicators extrapolated from the current literature. The evaluation of the results obtained determined the prerequisites for designing a replicable Circular Building model by 3D printing using a lignin-based biopolymer. The adoption and combination of these seemingly opposing themes was a key strength and asset to the project in terms of benefits such as energy savings, lead time, and cost savings at all life cycle stages.